Awareness programs towards people with disabilities in the school context, physical education and health. A systematic review of the last 10 years - Cristian Luarte-Rocha; Laura López-Casanova; Valentina Navarro-Gajardo; Yazmina Pleticosic; Rodrigo Sagredo-Aravena; Luis Felipe Castelli Correia de Campos; Kevin Isaias Campos Campos (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2023)
The objective was to analyze research from the last 10 years on disability awareness and inclusion programs in physical education classes. The electronic bibliographic databases Web of Science, Pubmed, EBSCO, Dialnet and Scielo were used following the PRISMA method for the search between the years 2011 and 2022. The search strategy yielded a total of 48 results, of which seven met the inclusion criteria. The selected articles are recent and the sample of participants is significant and of mixed gender. On the other hand, the intervention strategies described in these articles are of an experimental nature with more than seven days of intervention. The overall results obtained indicate a positive attitude change influenced by the type of technique used. The analysis of the selected studies shows that school awareness programs help improve the attitude of the school community towards people with disabilities, with greater effectiveness in the direct contact technique.